Power Production Waste. (1st October 2017) - Ye, Junpei; Zhu, Cheng; Zhang, Panyue; Zhang, Qian; Nabi, Mohammad; Wang, Xuan
Abstract : This review focuses on the research literature published in 2016 relating to power production waste that results from fossil fuel and nuclear power plants. It elaborates the characterization, reuse and disposal of power production wastes. The wastes from fossil fuel power plants have been divided into fly ash, flue gas desulfurization gypsum and waste catalyst. The environmental issues, associated with nuclear power plants and waste production are also reviewed.